ANALISIS KETERAMPILAN MENGAJAR GURU DALAM MEMOTIVASI BELAJAR SISWA DI SDIT RAUDHATURRAHMAH PEKANBARU - Afridayanti, Sintya; Guslinda; Permana, Dede (STKIP Subang, 2026)
This research was motivated by the existence of students who were less active, less focused, and lacked confidence during the learning process, indicating the need for effective teaching skills to improve students’ learning motivation. This study aimed to determine the relationship between teachers’ teaching skills and students’ learning motivation in Indonesian language learning for fourth grade students at SDIT Raudhaturrahmah Pekanbaru. This research used a qualitative approach with a descriptive research type. The subjects of this study consisted of one fourth-grade teacher and 23 students of class IV Al-Malik. Data were collected through observation, questionnaires, and interviews conducted over five meetings. The data were analyzed through data reduction, data presentation, and conclusion drawing using triangulation techniques. The results showed that the teacher had implemented eight basic teaching skills during the learning process, with the most dominant skills being reinforcement, variation, explaining, and classroom management skills. Students’ learning motivation showed fairly good results, with the most dominant indicators being appreciation in learning, interesting learning activities, and a conducive learning atmosphere. The findings also revealed that teachers’ teaching skills had a relationship with students’ learning motivation, indicating that teachers’ teaching skills play an important role in improving students’ learning motivation during the learning process.